Bone mineral density, kidney function, weight gain and insulin resistance in women who switch from TDF/FTC/NNRTI to ABC/3TC/DTG. Issue 2 (27th September 2020) - Ibrahim, F; Samarawickrama, A; Hamzah, L; Vincent, R; Gilleece, Y; Waters, L; Kegg, S; Barbini, B; Campbell, L; Post, FA
Abstract : Objectives: Tenofovir disoproxil fumarate (TDF) is associated with reduced bone mineral density (BMD). We evaluated changes in BMD in women who switched from TDF, emtricitabine and a nonnucleoside reverse transcriptase inhibitor (TDF/FTC/NNRTI) to abacavir, lamivudine and dolutegravir (ABC/3TC/DTG). Methods: We conducted a randomized controlled trial in which women aged ≥40 years were randomized 1:2 to continue TDF/FTC/NNRTI or switch to ABC/3TC/DTG. The primary endpoint was change in total hip BMD measured by dual‐energy X‐ray absorptiometry at week 48. Secondary endpoints were changes in BMD of the lumbar spine and femoral neck and markers of bone turnover and kidney function up to week 48. We conducted exploratory analyses of weight gain, insulin resistance and metabolic syndrome. Primary and secondary endpoints were analysed by linear regression, with multiple imputation for missing time points. Results: In all, 91 women [mean age = 50.4 (standard deviation [SD] = 6.6) years, median CD4 cell count = 600 (interquartile range: 479–800) cells/µL] were randomized. Women who switched to ABC/3TC/DTG maintained viral suppression and experienced improvements in total hip BMD (mean adjusted difference = 1%, P = 0.027) and lumbar spine BMD (3%, P = 0.002), with no change in specific markers of bone turnover or renal tubular function. Although participants in the ABC/3TC/DTG arm gained more weight (1.8 kg, P = 0.046), the switch strategy was not associated with reduced insulin sensitivity or new‐onset metabolic syndrome. Conclusions: Switching from TDF/FTC/NNRTI to ABC/3TC/DTG resulted in improved BMD. Although weight gain was common in women who switched from TDF/FTC/NNRTI to ABC/3TC/DTG, we did not detect adverse effects on glucose homeostasis. Larger studies need to confirm these findings.